2022
DOI: 10.1136/bmjsem-2022-001408
|View full text |Cite
|
Sign up to set email alerts
|

Health problems in national team cross-country skiers over a competitive season: a 17-week prospective cohort study

Abstract: ObjectiveFew long-term prospective studies have investigated health problems in elite competitive cross-country (XC) skiers. Hence, our objective was to compare the prevalence of health problems in national team XC skiers over a competitive season.MethodsForty national team XC skiers participated in this prospective, observational study. Two groups were characterised according to performance level: senior (n=18, ~26 years old, 9 women) and development (n=22, ~21 years old, 9 women). The skiers reported all and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We observed that delayed maturity status, shorter size and leg length are factors associated with increased injury risk in alpine skiers [9]. Conversely, higher age is a feature related to overuse injuries in cross-country skiing [22]. Additionally, we found that the jump agility test could be used as a predictor of injuries in youth ski racers, as proper timing of muscle actions and inter-and intra-muscular coordination of the relevant muscles is essential in injury prevention strategies.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We observed that delayed maturity status, shorter size and leg length are factors associated with increased injury risk in alpine skiers [9]. Conversely, higher age is a feature related to overuse injuries in cross-country skiing [22]. Additionally, we found that the jump agility test could be used as a predictor of injuries in youth ski racers, as proper timing of muscle actions and inter-and intra-muscular coordination of the relevant muscles is essential in injury prevention strategies.…”
Section: Discussionmentioning
confidence: 76%
“…Another 17-week prospective cohort study in a population of cross-country skiers showed a 9% of average weekly prevalence of injuries in females. Concerning age, athletes in development were less likely to suffer substantial and overuse injuries than senior athletes in general, and regarding sex differences, females were more likely to incur substantial health problems [22]. Reports from the last two Olympic Winter Games, 2018 and 2022, described an injury incidence ranging from 2 to 6 per 100 athletes [18], with five female injuries occurring in this sport [5].…”
Section: Cross-country Skiingmentioning
confidence: 99%